Trends in rates of trabeculectomy in England. - Keenan, T; Salmon, J; Yeates, D; Goldacre, M (2009)
AIMS: Rates of glaucoma surgery have declined in North America and continental Europe in recent years. The aim of this study was to examine trends over time and regional variation in rates of trabeculectomy in England. METHODS: The hospital in-patient enquiry (HIPE), hospital episode statistics (HES), and the Oxford record linkage study (ORLS) were analysed for annual trabeculectomy admissions between 1976 and 2004. RESULTS: Annual rates of admission for trabeculectomy rose 10-fold from 1976 to 1995: from 3.7 (95% confidence intervals 3.5-3.9) admissions per 100,000 population in 1976 to a peak of 38.7 (38.1-39.3) in 1995. Admission rates then declined sharply and have begun to reach a plateau at around 10.6 (10.3-10.9) in 2004. The highest surgical rates during the period 1997-2004 were found in the 80- to 84-year-old age group. Geographical analysis showed wide variation across local authority areas in annual rates of trabeculectomy, from 4 (2.3-5.2) to 33 (29.0-36.5) people per 100,000 population in 1998-2004. The rate of surgery by local authority showed little or no association with the level of social deprivation in each area. CONCLUSIONS: The rate of patients undergoing trabeculectomy increased substantially over 20 years. This was followed by a profound reduction in rates of trabeculectomy from 1995, which coincides with the introduction of new topical medications to reduce intraocular pressure. Wide regional variation in rates of trabulectomy was found, but there was no evidence of reduced access to glaucoma surgery in deprived areas.